Immunity to Pathogens Taught by Specialized Human Dendritic Cell Subsets - Geginat, Jens; Nizzoli, Giulia; Paroni, Moira; Maglie, Stefano; Larghi, Paola; Pascolo, Steve; Abrignani, Sergio (Frontiers in Immunology, 2015)
Dendritic cells (DC) are specialized antigen-presenting cells (APC) that have a key role in immune responses, because they bridge the innate and adaptive arms of the immune system. They mature upon recognition of pathogens and up-regulate MHC molecules and co-stimulatory receptors to activate antigen-specific CD4+ and CD8+ T-cells. It is now well established that DC are not a homogeneous population, but are composed of different subsets with specialized functions in immune responses to specific pathogens. Upon viral infections, plasmacytoid DC (pDC) rapidly produce large amounts of IFN-α, which has potent anti-viral functions and activates several other immune cells. However, pDC are not particularly potent APC and induce the tolerogenic cytokine IL-10 in CD4+ T-cells. In contrast, myeloid DC (mDC) are very potent APC and possess the unique capacity to prime naïve T-cells and consequently to initiate a primary adaptive immune response. Different subsets of myeloid DC with specialized functions have been identified. In mice, CD8α+ mDC capture antigenic material from necrotic cells, secrete high levels of IL-12, and prime Th1 and cytotoxic T cell responses to control intracellular pathogens. Conversely, CD8α- mDC preferentially prime CD4+ T-cells and promote Th2 or Th17 differentiation. BDCA-3+ mDC2 are the human homologue of CD8α+ mDC, since they share the expression of several key molecules, the capacity to cross-present antigens to CD8+ T-cells and to produce IFN-λ. However, although several features of the DC network are conserved between humans and mice, the expression of several relevant toll-like receptors as well as the production of cytokines that regulate T-cell differentiation are different. Intriguingly, recent data suggests specific roles for human DC subsets in immune responses against individual pathogens. The biology of human DC subsets holds the promise to be exploitable in translational medicine, in particular for the development of vaccines against persistent infections or cancer.